Racial inequity and other social disparities in the diagnosis and management of bladder cancer. (8th June 2022) - Hasan, Shaakir; Lazarev, Stanislav; Garg, Madhur; Mehta, Keyur; Press, Robert H.; Chhabra, Arpit; Choi, J. Isabelle; Simone, Charles B.; Gorovets, Daniel
Abstract: Background: We investigate the impact of gender, race, and socioeconomic status on the diagnosis and management of bladder cancer in the United States. Methods: We utilized the National Cancer Database to stratify cases of urothelial cell carcinoma of the bladder as early (Tis, Ta, T1), muscle invasive (T2–T3, N0), locally advanced (T4, N1–3), and metastatic. Multivariate binomial and multinomial logistic regression analyses identified demographic characteristics associated with stage at diagnosis and receipt of cancer‐directed therapies. Odds ratios (OR) are reported with 95% confidence intervals. Results: After exclusions, we identified 331, 714 early, 72, 154 muscle invasive, 15, 579 locally advanced, and 15, 161 metastatic cases from 2004–2016. Relative to diagnosis at early stage, the strongest independent predictors of diagnosis at muscle invasive, locally advanced, and metastatic disease included Black race (OR = 1.19 [1.15–1.23], OR = 1.49 [1.40–1.59], OR = 1.66 [1.56–1.76], respectively), female gender (OR = 1.21 [1.18–1.21], OR = 1.16 [1.12–1.20], and OR = 1.34 [1.29–1.38], respectively), and uninsured status (OR = 1.22 [1.15–1.29], OR = 2.09 [1.94–2.25], OR = 2.57 [2.39–2.75], respectively). Additional demographic factors associated with delayed diagnosis included older age, treatment at an academic center, Medicaid insurance and patients from lower income/less educated/more rural areas (all p  < 0.01). Treatment at a non‐academic center, older age, women, Hispanic and Black patients, lower income and rural areas were all less likely to receive cancer‐directed therapies in early stage disease (all p  < 0.01). Women, older patients, and Black patients remained less likely to receive treatment in muscle invasive, locally advanced, and metastatic disease (all p  < 0.01). Conclusion: Black race was the strongest independent predictor of delayed diagnosis and substandard treatment of bladder cancer. Abstract : In a robust multivariable analysis of the national cancer database, among demographic characteristics we found that black patients were most significantly, consistently, and independently associated with both late diagnosis and use of non‐standard therapies.